Public health significance of atherosclerosis - Vesna Lazić; Biljana Mijović; Miloš Maksimović (Биомедицинска истраживања, 2020)
Atherosclerosis is the leading cause of cardiovascular disease (CVD) worldwide. Recently, mortality and morbidity from CVD have shown a trend in its occurrence in earlier years, while these diseases have been associated with older age until recently. In developed countries, mortality from diseases caused by atherosclerosis has decreased over the last 50 years. However, such a trend is not reflected in both underdeveloped and developing countries where mortality remains high. Risk factors have been identified and their control can influence the reduction in morbidity and mortality from CVD associated with atherosclerosis. Among these, the so-called variable risk factors are the following: increased concentration of LDL cholesterol fraction (LDL) and/or decreased concentration of HDL cholesterol fraction (HDL), hypertension, cigarette consumption, diabetes mellitus/metabolic syndrome, improper diet, while genetic predisposition is still considered to be an invariable risk factor. In order to reduce the incidence of atherosclerosis, the World Health Organization recommends a two-pronged approach that includes public health interventions to reduce population risk factors and medical interventions for individuals at high risk with stricter surveillance of risk factors. Examples of multisectoral public health interventions include increasing taxes on cigarettes and alcohol, followed by a massive campaign to promote physical activities and healthy diet, that is to promote healthy lifestyles.
Keywords: atherosclerosis; cardiovascular diseases; public health significance